Student Dropout at the Hellenic Open University – Evaluation of the graduate program: Studies in Education - Vergidis, Dimitris; Panagiotakopoulos, Chris (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2002)
This study traces the root causes of dropout rates in one post-graduate course “Studies in Education,” offered by the Hellenic Open University (HOU). From our research findings, it was found that the main cause of dropping out stem from a combination of adult learners’ obligations, specifically balancing their academic workload with their employment commitments and family obligations (mainly for female students). The second reason for dropout rates among adult distance education learners include students’ miscalculation of the available time for studying and their underestimation of the extra effort required for effective learning. These reasons can be compared to the educational material, which, in general, was not considered overly difficult and did not appear to compel students to abandon their studies.